Purchasing and Receiving Process in Procurement of Goods at JHL Solitaire Gading Serpong Hotel - Putra, Sangga Munggaran; Prianti, Diani Mustika (Journal of Indonesian Tourism and Policy Studies, 2023)
Purchasing and Receiving are two of the many divisions in the finance department, which are the main doors for procuring goods at hotels. These two divisions must ensure that the products ordered and received are high quality and comply with operational standards to create customer satisfaction. This study aims to provide an overview of the processes carried out by the purchasing and receiving divisions in the procurement of goods at the JHL Solitaire Hotel. The research method used is qualitative. The technique gets direct observations at the JHL Solitaire Hotel, interviews, and literature studies. The results of this study are that the purchasing division is fully responsible for procuring goods by connecting users with vendors according to the information in the Purchase Order (PO). Furthermore, the receiving division is responsible for receiving and storing goods. In this case, the receiving division will receive the goods and check the conformity of the goods according to the PO, then distribute the goods to the relevant department or storekeeper. If the goods are not taken immediately, the storekeeper will store the goods in the warehouse using the First In First Out (FIFO) system so that the quality of the goods is maintained. Accuracy in supervision and good coordination between the three sections will minimize the occurrence of errors in the operational function of the hotel. Future researchers are advised to be able to conduct research with valid data regarding the effectiveness of purchasing and receiving procuring goods at JHL Solitaire Hotel.